MANAJEMEN SUMBER DAYA MANUSIA GURU DALAM PENGUATAN PROFIL PELAJAR PANCASILA DI SEKOLAH DASAR NEGERI BATURSARI 5 KECAMATAN MRANGGEN KABUPATEN DEMAK - Muhamad Iksan; Bunyamin; Ghufron Abdullah (STKIP Subang, 2023)
Implementation of education to strengthen the profile of Pancasila students is education with absolute character strengthening and is the main thing that must be considered by all parties in the conditions of life of the nation and state. The sub focus of this research is on planning, organizing, directing, and supervising inherent in every creative organizational operational function to achieve goals effectively and efficiently in strengthening the profile of Pancasila students. The research uses a qualitative approach using a multi-case study design. Data collection is done by interviews, observation and documentation. Research informants were school principals, school supervisors, teachers, school committee members and students. Data obtained from informants and research subjects were analyzed using qualitative data. Meanwhile, checking the validity of the data uses source triangulation. Based on the research results and theories of teacher HR Management in strengthening the profile of Pancasila students at SD Negeri Batursari 5, Mranggen District, Demak Regency, it can be concluded that; (a) placement and assignment of teacher human resources as learning facilitators which are then determined in a school principal's decree to become a learning committee task force with the aim of creating a system in the education unit to become an open ecosystem, participation of community involvement as a learning organization; (b) organizing learning committees in work units holistically within the ecosystem of organizing educational units, independently conducting periodic self-reflection activities on weekends; (c) directing by creating an education unit system to become an ecosystem and based on character and abilities that are built in the daily life of each individual teacher and student through the culture of educational organizational units and; (d) the supervisory function by carrying out supervision and Teacher Performance Assessment (PKG) to find out quickly and precisely the problems being faced by teachers and used as a strategic plan in determining the steps that need to be taken in achieving the desired performance goals. The advice given to teacher human resource management in strengthening the profile of Pancasila students is that teachers as learning facilitators who are appointed in the learning committee task force concretely and administratively prepare planning, implementation and monitoring programs of activities so that they do not rely on one of the active units in the learning committee task force